Dental Abnormalities in Pituitary Dwarfism: A Case Report and Review of the Literature. (28th March 2017) - Ferrante, Franco; Blasi, Sergio; Crippa, Rolando; Angiero, Francesca
Abstract : Hypopituitarism is a disorder caused by a reduced level of trophic hormones that may be consequent on different destructive processes. The clinical manifestations depend on the type of hormone involved. A deficiency of growth hormone (GH) in children causes the lack of growth known as pituitary dwarfism. The case is reported of a patient with pituitary dwarfism, multiple dental anomalies, functional prosthetic problems, and a revision of the literature. She was subjected to prosthetic rehabilitation without surgical intervention, using zirconium substructures, thus eliminating the potential complications that may require trauma surgery. The therapeutic approach adopted led to excellent results and restored an aesthetic smile.